Can Offering More Grade Control Improve Middle School Students' Motivation?. Issue 3 (4th May 2022) - Morris, Sarah R.; Barton, Alison L.
Abstract: Students' academic motivation decreases in middle grades; specifications grading (SG) may be one way to boost students' motivation by offering greater agency. In this mixed-methods, quasi-experimental study, we compared SG with traditional grading methods among 69 low-income, 8 th grade math students. Results indicate that students in SG classes have greater anticipation of success, greater interest, and trended toward a greater sense of self-efficacy than those in traditionally graded classes. Qualitative remarks from SG participants indicate a greater sense of control and decreased stress in math, as well as an emphasis on learning over performance. Although further research is needed, our results offer instructional implications regarding ways to offer students more control through grading systems.